2017
DOI: 10.1161/jaha.117.006304
|View full text |Cite
|
Sign up to set email alerts
|

Significant Associations of Neurological Complications of Herpes Zoster With Stroke in Rheumatoid Arthritis Patients

Abstract: BackgroundAccumulating evidence suggests an increased risk of stroke after herpes zoster (HZ). This risk is elevated in immunocompromised patients. The incidence of HZ in Asia is higher than in Western countries. However, the epidemiology of HZ and HZ‐related stroke among rheumatoid arthritis (RA) patients in Asia remains unclear.Methods and ResultsWe conducted a retrospective cohort study using a population‐based database to investigate the epidemiology of HZ in RA patients in Taiwan during the period of 2000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 54 publications
2
13
0
1
Order By: Relevance
“…It was reported that there was an age‐specific decrease in VZV memory CD4 cells, so immunosenescence may be the key cause which leads to the increase of VZV infection and reactivation in the elderly . Previous studies showed that in Taiwan age is also a major risk factor for HZ . We obtained a similar result.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…It was reported that there was an age‐specific decrease in VZV memory CD4 cells, so immunosenescence may be the key cause which leads to the increase of VZV infection and reactivation in the elderly . Previous studies showed that in Taiwan age is also a major risk factor for HZ . We obtained a similar result.…”
Section: Discussionsupporting
confidence: 81%
“…25 Previous studies showed that in Taiwan age is also a major risk factor for HZ. 17 We obtained a similar result.…”
Section: Ta B L E 1 Characteristics Among Groupssupporting
confidence: 73%
See 1 more Smart Citation
“…The present review has contributed 29 studies,25–51 among them 2 meta-analyses,52 53 expanding the data on the incidence of HZ in AIIRD (table 3). Eleven studies included a control group 25 28 34 39 40 44–46 49–51. Based on the analysis of 21 studies including 894 891 patients, pooled IR and pooled IRR were calculated for patients with AIIRD in general and for specific disease subtypes (figure 2; s upplementary file table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Herpes zoster (HZ) is a prevalent and potentially debilitating illness caused by varicella zoster virus (VZV) reactivation [ 1 ] ; its common complications include post-herpetic neuralgia, ophthalmic involvement, and neurological sequelae. [ 2 , 3 ] Patients with rheumatoid arthritis (RA) have increased risk for HZ, [ 4 , 5 ] and iatrogenic risk factors include glucocorticoids, methotrexate, and biologic agents used to treat RA. [ 6 ] Weakened host cell-mediated immunity is an important etiologic factor for varicella zoster reactivation.…”
Section: Introductionmentioning
confidence: 99%